Case Report: A usual procedure in an unusual situation: a patient with a rare Ehlers Danlos/osteogenesis imperfecta overlap undergoing aortic valve replacement - Nunez-Ordonez, Nicolas; Amado-Olivares, Andrés F.; Jimenez-Ordonez, Andrés F.; Obando, Carlos; Chalela, Tomas; Senosiain, Julián; Sandoval, Nestor; Camacho-Mackenzie, Jaime; Villa-Hincapié, Carlos (Frontiers in Cardiovascular Medicine, 2025)
Connective tissue disorders are known to cause cardiac and vascular complications. We present the case of a 37-year-old female patient with a rare Ehlers Danlos/Osteogenesis Imperfecta Overlap Syndrome, referred to cardiac surgery with aortic valve regurgitation, who underwent a successful Biological Surgical Aortic Valve Replacement (SAVR). A multidisciplinary, patient-centered, heart-team approach is essential in managing patients with rare genetic disorders to optimize postoperative outcomes. Adult cardiac surgeons must become familiar with genetic syndromes and their implications for improving perioperative outcomes.